(untitled) (Revista científica Olimpia, 2020)
It is intended to examine criteria that the perception of the time and the velocity in the offensive actions and defensives of the Karate Do, as from his not fragmented dynamics and dialectics, during his process of technical training and tactics characterize in the present article. They offer elements contentivos of observation and analysis to the processes that interact within the sportsman’s system of preparation. Split of some criteria that the study and reasoning of this component of preparation evidence, followed of the epistemological foundation, theoretic sustenances methodological, laws and beginnings that vouch for it.